Organizational behavior : an evidence-based approach - Luthans, Fred; Luthans, Brett C.; Luthans, Kyle W. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
Contrary to the common saying: we do want you to judge this new edition of Organizational Behavior by its front cover. Specifically, featured is that this is the 14th edition, it takes an "Evidence-Based Approach," and similar to the previous edition there are now three Luthans authors. This 14th edition is based on the foundation provided by the first mainline text which has become the classic for the study and understanding of organizational behavior. However, by taking an evidence based approach, this insures that, even though a classic, this new edition adds the most recent and relevant research to the most extensive, up-to-date reference-base of any organizational behavior text. By adding the two closely related authors (professor sons) literally pumps "new blood" into the sustainability of this classic text by Fred Luthans.Finally, this new edition recognizes that even though the theoretical framework and coverage largely remains, the context of organizational behavior is rapidly changing. This new edition reflects the "New Age" environment, but still holds to the premise that in today's organizations, success and competitive advantage still comes from the understanding, prediction, and effective management of human resources. With this new edition we invite you to continue the never-ending journey guided by the best organizational behavior theory, research, and application.